Organic manure and inorganic fertilizer management for sustainable sweet potato (Ipomoea batatas) production - Islam, Md. Monirul; Paul, T. K.; Nik Ab. Majid, Nik Muhamad (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The experiment was conducted to study the effect of organic manure and chemical fertilizers on soil properties and sweet potato yield at Grey Terrace soil. There were seven treatments - T1 (Control), T2 (100% recommended dose of fertilizers, RDF), T3 (Poultry manure, PM@ 3t ha-1+ rest from RDF), T4 (Cowdung, CD @ 6 t h-1+ rest from RDF), T5 (PM@ 3 t ha-1+70% RDF), T6 (CD@ 6 t h-1+ 70% RDF) and T7 (Farmer’s practice, FP). The highest sweet potato yield (22.7 t ha-1) was obtained in T3 (PM@ 3t ha-1+ rest from RDF). Physical properties improved by incorporation of organic manure having the better in T4 and T6. Highest available N,P,K and S were found in T3. Poultry manure 3t ha-1 or Cowdung 6t ha-1 + reduced recommended dose of chemical fertilizer can be recommended for cultivation of potato and to maintain soil health in Grey Terrace soil.